Selective CNS targeting and distribution with a refined region-specific intranasal delivery technique via the olfactory mucosa - Maigler, Frank; Ladel, Simone; Flamm, Johannes; Gänger, Stella; Kurpiers, Barbara; Kiderlen, Stefanie; Völk, Ronja; Hamp, Carmen; Hartung, Sunniva; Spiegel, Sebastian; Soleimanizadeh, Arghavan; Eberle, Katharina; et al. (Pharmaceutics, 2021)
Intranasal drug delivery is a promising approach for the delivery of drugs to the CNS, but too heterogenous, unprecise delivery methods without standardization decrease the quality of many studies in rodents. Thus, the lack of a precise and region-specific application technique for mice is a major drawback. In this study, a previously developed catheter-based refined technique was validated against the conventional pipette-based method and used to specifically reach the olfactory or the respiratory nasal regions. This study successfully demonstrated region-specific administration at the olfactory mucosa resulting in over 20% of the administered fluorescein dose in the olfactory bulbs, and no peripheral bioactivity of insulin detemir and Fc-dependent uptake of two murine IgG1 (11C7 and P3X) along the olfactory pathway to cortex and hippocampus. An scFv of 11C7 showed hardly any uptake to the CNS. Elimination was dependent on the presence of the IgG’s antigen. In summary, it was successfully demonstrated that region-specific intranasal administration via the olfactory region resulted in improved brain targeting and reduced peripheral targeting in mice. The data are discussed with regard to their clinical potential.